Development of a Guided Inquiry-Based E-Module Integrated with KingDraw on Isomerism to Improve Motivation and Learning Outcomes - Hayati, Nisa Nur; Rahardjo, Sentot Budi; Susilowati, Endang (Universitas Sebelas Maret, 2026)
This research aims to develop an e-module, test the feasibility of the e-module, and test the effectiveness of the guided inquiry-based e-module integrated with KingDraw on isomerism to improve motivation and learning outcomes. This research and development which refers to the Borg & Gall development model which consists of 10 steps and was conducted in three senior high schools in Surakarta. Data collection techniques were carried out by observation, interviews and test questionnaires. The effectiveness test used a pretest-posttest design group. Data on motivation and learning were analyzed using normalized gain and SPSS, including normality, homogeneity, and independent sample t-tests. The results show that the guided inquiry-based chemistry e-module integrated with KingDraw was successfully developed through ten Borg and Gall stages and declared feasible as supporting teaching material. Feasibility was demonstrated through expert validation using the Aiken index on media (V = 0.87), material (V = 0.85), and language (V = 0.88) aspects. Guided inquiry-based e-modules with the help of KingDraw have been proven to be more effective than conventional methods in improving students' motivation and learning outcomes, as shown by the higher N-gain value of the experimental class compared to the control class, both in learning outcomes (0.553 > 0.246) and learning motivation (0.673 > 0.216). In addition, the results of the independent t-test with a sig. value of 0.00 indicate that the use of e-modules provides a significant difference to students' motivation and learning outcomes.